Thermal Transmittance of Internal Partition and External Facade LSF Walls: A Parametric Study - Santos, Paulo (2019)
Light steel framed (LSF) construction is becoming widespread as a quick, clean and flexible construction system. However, these LSF elements need to be well designed and protected against undesired thermal bridges caused by the steel high thermal conductivity. To reduce energy consumption in buildings it is necessary to understand how heat transfer happens in all kinds of walls and their configurations, and to adequately reduce the heat loss through them by decreasing its thermal transmittance (U-value). In this work, numerical simulations are performed to assess di erent setups for two kinds of LSF walls: an interior partition wall and an exterior facade wall. Several parameters were evaluated separately to measure their influence on the wall U-value, and the addition of other elements was tested (e.g., thermal break strips) with the aim of achieving better thermal performances. The simulation modeling of a LSF interior partition with thermal break strips indicated a 24% U-value reduction in comparison with the reference case of using the LSF alone (U = 0.449W/(m2.K)). However, when the clearance between the steel studs was simulated with only 300 mm there was a 29% increase, due to the increase of steel material within the wall structure. For exterior facade walls (U = 0.276W/(m2.K)), the model with 80 mm of expanded polystyrene (EPS) in the exterior thermal insulation composite system (ETICS) reduced the thermal transmittance by 19%. Moreover, when the EPS was removed the U-value increased by 79%.